The politics of affirmative action: Ethnicity, equity, and state-business relations in Malaysia - Edmund Terence Gomez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Malaysia provides for interesting paradoxes. Poverty was reduced by adopting a horizontal perspective to policy planning through affirmative action targeting one ethnic group lagging economically in society. However, outcomes of affirmative action include growing wealth and income disparities, a problem this policy was supposed to address. Furthermore, the government has not been able to dictate the pattern of enterprise development despite a variety of state-business relations to shape the evolution of Malay-owned enterprises. This study assesses the efficacy of horizontal-based policy instruments to redress ethnic inequalities and wealth disparities. It focuses on how politics influenced policy implementation through state-business relations and highlights how inequalities are structurally shaped but ethnically expressed, provoking different responses between and within ethnic groups about affirmative action. The results ascertain whether social cohesion is best pursued through vertical-type policies that address structural factors contributing to socioeconomic inequalities, thereby allowing communities to transcend class and ethnic differences.
Keywords: D63; D72; D73; D74; 330; politics; horizontal-based policies; enterprise development; affirmative action; state- business relations